2008
DOI: 10.1111/j.1745-7262.2008.00388.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of vardenafil in Asian men with erectile dysfunction

Abstract: Vardenafil (10 mg) is a highly effective and well-tolerated treatment for moderate ED in Asian men. These results add to the increasing amount of data demonstrating the safety and efficacy of vardenafil for the treatment of ED in a range of patient populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
1
5
0
Order By: Relevance
“…In agreement with this study, a recent meta-analysis found that, in a pooled analysis of PDE5 inhibitors, treatment was more effective in Caucasians compared with Asians 36 . However, a smaller (N = 334 patients; 264 vardenafil, 70 placebo) study investigating vardenafil efficacy in Asian men reported a significant increase in IIEF-EF score, which was similar to that seen in previous studies in Caucasians 37 . Direct comparisons between studies are difficult to make owing to differences in protocols; thus, further investigation is warranted to explore these potential ethnic differences and their causes.…”
Section: Discussionsupporting
confidence: 88%
“…In agreement with this study, a recent meta-analysis found that, in a pooled analysis of PDE5 inhibitors, treatment was more effective in Caucasians compared with Asians 36 . However, a smaller (N = 334 patients; 264 vardenafil, 70 placebo) study investigating vardenafil efficacy in Asian men reported a significant increase in IIEF-EF score, which was similar to that seen in previous studies in Caucasians 37 . Direct comparisons between studies are difficult to make owing to differences in protocols; thus, further investigation is warranted to explore these potential ethnic differences and their causes.…”
Section: Discussionsupporting
confidence: 88%
“…Although side effects do occur with vardenafil (most notably headache, flushing, indigestion and nasal congestion), providing that the drug is used in line with the labeling recommendations, there is no convincing evidence in the literature of any significant safety issue, including cardiovascular, visual and aural safety [105–127].…”
Section: Drugs Which Are Effective When Administered Systemicallymentioning
confidence: 99%
“…These included four RCTs of sildenafil, [31][32][33][34] two RCTs of vardenafil, 35,36 four RCTs of tadalafil, [37][38][39][40] two RCTs of udenafil 41,42 and two RCTs of mirodenafil. 43,44 The efficacy and safety of two novel PDE-5 inhibitors, mirodenafil and udenafil, were evaluated only in Korean men.…”
Section: Medical Treatment Of Ed In Asiamentioning
confidence: 99%
“…35,36 The first such study was performed in six countries or regions: Malaysia, Singapore, Thailand, the Philippines, Hong Kong (China) and Indonesia. 35 In this study, 358 men with ED were randomly assigned to receive vardenafil 10 mg or placebo for 12 weeks. The primary efficacy variables were the IIEF-EF and the sexual encounter profile (SEP) questions related to penetration (SEP2) and intercourse completion (SEP3).…”
Section: Efficacy and Safety Of Sildenafilmentioning
confidence: 99%
See 1 more Smart Citation